Strategi Pengembangan Karakter Leadership Siswa melalui Program Berbasis Pembinaan - Anisa, Triana May Latul; Pramitha, Devi (J-MPI (Jurnal Manajemen Pendidikan Islam), 2024)
The principal’s strategy in shaping student character, especially leadership character, is very important to create a generation of leaders with quality and integrity. With the right strategy, principals can direct students to develop their leadership potential, motivate them to take responsibility, and teach important ethical values in leadership. This study has the objectives of (1) Knowing the principal’s strategic planning to develop student leadership character at SMP Alam Mutiara Umat Tulungagung (2) To describe the implementation of the principal’s strategy to develop student leadership character at SMP Alam Mutiara Umat Tulungagung (3) Knowing the evaluation of the principal’s strategy school to develop student leadership character at Alam Mutiara Umat Middle School. The research method used is a qualitative approach with the type of case study research where in this case the researcher fully understands the phenomena that occur and in maintaining the authenticity of the data, the researcher is actively involved and goes directly to the field. Data collection was carried out by means of semi-structural interviews, observation and documentation. Respondents who were used as data sources were school principals, deputy heads of student affairs, deputy heads of public relations, deputy heads of curriculum and deputy heads of infrastructure. The data that has been obtained will be processed using the process of data reduction, data presentation and drawing conclusions. The credibility of the data is done by checking the triangulation procedure of data sources and techniques. The results of the study revealed that the principal’s strategy for developing student leadership character at Alam Mutiara Umat Middle School, Tulungagung Regency was: (1) The principal made a plan by establishing student leadership character development programs (2) in implementing the principal’s strategy optimizing the leadership character development program students through forum meetings (3) Evaluation of the principal’s strategy for developing student leadership character by way of performance appraisal to find out whether the program being implemented can develop student leadership character.